Developing Creative Thinking in School Students through National Embroidery-Based Design Projects - Nematova Tursuntosh Alisher qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the role of national embroidery-based design projects in fostering creative thinking among school students. Incorporating traditional embroidery into practical art projects not only enhances students’ artistic skills but also develops problem-solving abilities, aesthetic awareness, and cultural identity. The article discusses pedagogical approaches, project organization, and the integration of traditional patterns into modern design. Research shows that embroidery-based projects provide a holistic platform for nurturing creativity, critical thinking, and cultural appreciation in students.